Human resource management effects on sustainability of high-tech companies: what Lithuania and South Korea can learn from each other - Mindaugas Laužikas; Aistė Miliūtė (Insights into Regional Development)
The literature on the role of intellectual capital on the development of an economy, industry or business is well established (Carnevale and Smith 2013, Lauzikas and Miliute 2017, Kavurmaci 2018, Koehorst et al. 2019, Schoff and Ito, 2019, Koehorst et al. 2019, and etc.). However, the scarcity of holistic transdisciplinary studies regarding factors/ conditions that are critical to unleash the potential of human resources, such as HR Management innovation (Gonera and Pabst 2019, Lee et al. 2019, and etc.), innovation culture (Isaacs et al. 2019, Halim et al. 2019, Sull et al. 2019, Lauzikas and Mokseckienė 2013, Lauzikas and Miliute 2019a, and etc.), creative leadership (Abdi et al. 2018, Jin et al. 2019, Collett et al. 2019, and etc.), modern technologies (Deloitte 2019, Lee et al., Kim et al. 2019, and etc.), new collaboration forms (Kane et al. 2019, Isaacs and Ancona, 2019, Lauzikas and Miliute 2019b, and etc.), social value-added (Wikhamn 2019, Marwede and Herstatt 2019, and etc.) calls for the untapped research potential in the area of Human Resource Management innovation, based on the development stage and peculiarities of cultural and social norms of an economy. The purpose of the present publication is to identify the key drivers of human capital-driven high-tech industries and understand how the Human Resource Management department could help strengthen competitive advantages of high-tech companies in South Korea and Lithuania. The research question is what Human Resource Management innovations are necessary to realign the innovation culture with a specific cultural/ social context and a corresponding economic/ business development stage in order to improve companies’ competitive position in light of digital transformation of the market. The qualitative semi structured expert interviews led to assumptions and results which explain how human capital links the culture and innovation and why the percentage of commercialized creative ideas in South Korean companies is higher than in Lithuanian companies. In spite of practical and value adding implications and recommendations to both top management and experts of Governmental policies and programs, a more extensive quantitative research should be provided in the next articles of the same series to feel better the global market trends and understand demographic characteristics that affect the organizational behaviour patterns and HRM decisions.